Chinese social media suggest decreased vaccine acceptance in China: An observational study on Weibo following the 2018 Changchun Changsheng vaccine incident. Issue 13 (17th March 2020) - Hu, Dian; Martin, Christine; Dredze, Mark; Broniatowski, David A.
Highlights: We use Weibo to study vaccine acceptance in China after the 2018 vaccine scandal. Messages pertaining to vaccines expressed more distrust of government after the scandal. Sentiment of self-reports of vaccination changed from positive to concerned. Long-term effect of the scandal shows vaccine acceptance in China may be decreasing. Abstract: China is home to the world's largest population, with the potential for disease outbreaks to affect billions. However, knowledge of Chinese vaccine acceptance trends is limited. In this work we use Chinese social media to track responses to the recent Changchun Changsheng Biotechnology vaccine scandal, which led to extensive discussion regarding vaccine safety and regulation in China. We analyzed messages from the popular Chinese microblogging platform Sina Weibo in July 2018 (n = 11, 085), and August 2019 (n = 500). Thus, we consider Chinese vaccine acceptance, before, during, immediately after, and one year after the scandal occurred. Results show that expressions of distrust in government pertaining to vaccines increased significantly during and immediately after the scandal. Self-reports of vaccination occurred both before, and one year after, the scandal; however, these self-reports changed from positive endorsements of vaccination to concerns about vaccine harms. Data suggest that expressed support for vaccine acceptance in China may be decreasing.